2021
DOI: 10.3168/jds.2020-18820
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological, immunological, and histological changes in the gut of Salmonella Enteritidis-challenged rats fed goat cheese containing Lactobacillus rhamnosus EM1107

Abstract: Cheeses are able to serve as suitable matrices for supplying probiotics to consumers, enabling appropriate conditions for bacteria to survive gastric transit and reach the gut, where they are assumed to promote beneficial processes. The present study aimed to evaluate the microbiological, immunological, and histological changes in the gut of Salmonella Enteritidis-challenged rats fed goat cheese supplemented with the probiotic strain Lactobacillus rhamnosus EM1107. Thirty male albino Wistar rats were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Studying the animal gut microbiota, Moeller et al (2018) reported that the composition of gut microbiota was different among animals. There are extremely significant differences among the diversity and richness of gut microbiota of horses ( Mshelia et al, 2018 ), rats ( Rolim et al, 2021 ), geese ( Wang et al, 2020 ), cows ( Uchiyama et al, 2020 ), and goats ( Liu et al, 2020 ). To date, there have been only few 16S ribosomal RNA (rRNA) gene sequencing technology-based studies, which have investigated the gut microbiota of small ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the animal gut microbiota, Moeller et al (2018) reported that the composition of gut microbiota was different among animals. There are extremely significant differences among the diversity and richness of gut microbiota of horses ( Mshelia et al, 2018 ), rats ( Rolim et al, 2021 ), geese ( Wang et al, 2020 ), cows ( Uchiyama et al, 2020 ), and goats ( Liu et al, 2020 ). To date, there have been only few 16S ribosomal RNA (rRNA) gene sequencing technology-based studies, which have investigated the gut microbiota of small ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed beneficial aspects of a probiotic cheese on the gut microbiota. Supplementation of goat cheese containing the probiotic strain L. rhamnosus EM1107 to Salmonella Enteritidis‐challenged rats significantly reduced Salmonella colonization in the intestinal lumen and increased the growth of beneficial bacteria: Blautia and Lactobacillus (Rolim et al., 2021). In a randomized controlled trial, consumption of cheese (30 g/day) containing B. lactis Bi‐07 by 30 constipated women showed relief from constipation (Favretto et al., 2013).…”
Section: Health Benefits/physiological Effects Of Probiotic Dairy Productsmentioning
confidence: 99%